Mapping Designpreneur Paradigm for Sustainability Housing of Ministerial in Nusantara Capital City (IKN) - Purnama, Ika Yuni; Phetorant, DJ. Dimas; Mestika, Gelar Gelora; Sunarjo, Richard Andre; Radhika, Raka Daniswara (Pandawan, 2025)
Designpreneurs (a combination of design and entrepreneurs) have gained attention as an innovation paradigm that integrates design creativity with business value, playing a significant role in driving innovation and sustainable value creation. As the national creative economy and the IKN smart design agenda develop, it is important to evaluate research trends related to this concept. This study aims to map designpreneurship literature through bibliometric analysis, identifying publication trends, dominant themes, and key actors in this field. Data were taken from the Dimensions database (2000–2025), covering 45 articles, analyzed using VOSviewer to reveal collaboration patterns (country, institution, author) and keywords. The publication trend has increased sharply since 2016, reaching 10 articles in 2024. Indonesia has emerged as a major hub with strong collaborations with Malaysia, Japan, and China. The Bandung Institute of Technology was identified as the most productive institution. The journals Design, Economics and Innovation, Review of Managerial Science, and Journal of the Knowledge Economy are at the forefront of publications. Dominant research themes include the integration of design thinking, business innovation, and sustainability, indicating a focus on sustainable design innovation. This study presents a comprehensive mapping of designpreneurship literature, strengthening the concept of design and entrepreneurship synergy in creative innovation. These findings are relevant to the design strategy of ministerial position houses in the IKN based on local wisdom and sustainability.